Comparison of 25- and 27-Gauge Pars Plana Vitrectomy in Repairing Primary Rhegmatogenous Retinal Detachment. (25th June 2018) - Otsuka, Keiko; Imai, Hisanori; Fujii, Ayaka; Miki, Akiko; Tagami, Mizuki; Azumi, Atsushi; Nakamura, Makoto
Abstract : Aim . To compare the anatomic and visual outcomes of 25-gauge (25G), and 27-gauge (27G) transconjunctival sutureless pars plana vitrectomy (TSV) for the management of primary rhegmatogeneous retinal detachment (RRD). Design . A retrospective nonrandomized clinical trial. Methods . A retrospective comparative analysis of 62 consecutive eyes from 62 patients with 6 months of follow-up was performed. Results . Thirty-two patients underwent 25G TSV, and 30 patients underwent 27G TSV for the treatment of primary RRD. There was no significant difference in baseline demographic and preoperative ocular characteristics between the two groups. The initial and final anatomical success rates were 93.8% and 100% in 25G TSV and 96.7% and 100% in 27G TSV, respectively (p = 1 andp = 1, resp.). Preoperative best-corrected visual acuity (BCVA) (logMAR) was 0.44 ± 0.69 and 0.38 ± 0.61 for 25G and 27G TSV, respectively (p = 0.73 ). The final follow-up BCVA was 0.07 ± 0.25 and −0.02 ± 0.17 for 25G and 27G TSV, respectively (p = 0.16 ). The final BCVA was significantly better than the preoperative BCVA in both groups (p = 0.02 andp = 0.002, resp.). Preoperative intraocular pressure (IOP) (mmHg) was 13.0 ± 3.5 in 25G TSV and 14.3 ± 2.8 in 27G TSV (p = 0.11 ). IOP did not statistically significantly change in both groups during the follow-up period (p = 0.63 andp = 0.21, resp.). Conclusion . The 27G TSV system is safe and useful for RRD treatment as 25G TSV.